\Tilde{B_{k}^{ij}} = f(B^{i})_{k} + (1 - \lambda) f(B^{j})_{k} \\
\Tilde{y^{ij}} = \lambda y^{i} + (1 - \lambda) y^{j}

This is my current equation. Unfortunately, the tilde is not directly placed on the B, but instead floats above the supercript. How to fix this?

Tilde example

  • Welcome to tex.sx. The problem is in the input. The tilde should be placed above only the letter it modifies: \Tilde{b}_{k}... or \Tilde{y}^{ij}. Commented May 19, 2023 at 13:47
  • 2
    Note that \Tilde and \tilde are exactly the same.
    – egreg
    Commented May 19, 2023 at 15:08

1 Answer 1


Welcome to TeX.SE!

Something like this?

enter image description here


\Tilde{B}_{k}^{ij} = f(B^{i})_{k} + (1 - \lambda) f(B^{j})_{k} \\
\Tilde{y}^{ij} = \lambda y^{i} + (1 - \lambda) y^{j}

Observe, where are } : \Tilde{B}_{k}^{ij} instead of \Tilde{B_{k}^{ij}}.

BTW, it will be helpful, if you would extend your code fragment to complete small document.

  • Thank you for the welcome and the nice answer! That's exactly what I was looking for. I will keep in mind having a MWE. Commented May 19, 2023 at 14:42

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .